Does pain deteriorate working life expectancy in aging workers? - Lee, Wanhyung (J Occup Health, 2016)
OBJECTIVES: Many aging workers wish to continue working as long as they can for a better life in the future. However, symptoms of pain are a key obstacle in the continuation of work among older workers. The impact of pain on work is understudied. Thus, we investigated the relationship between pain characteristics (total site and severity) and aging workers' working life expectancy scale (WoLES) in Korea. METHODS: We included 1,979 participants (1,175 men and 804 women) from a well-established survey of a nationally representative population: the Korean Longitudinal Study of Ageing. A self-questionnaire was used to assess pain characteristics and WoLES. Odds ratios (ORs) and 95% confidence intervals (CIs) for the lower-WoLES group were calculated using multiple logistic regression models. RESULTS: Compared with the absence of pain, ORs and 95% CIs of the lower-WoLES group were increased, as follows: 1 pain site, 1.75 (1.20-2.55); 2 pain sites, 1.99 (1.32-3.03); 3 or more pain sites, 2.28 (1.51-3.42); mild pain, 1.74 (1.32-2.61); moderate pain, 2.02 (1.28-3.22); and severe pain, 2.12 (1.46-3.08). The statistical trend was significant in both total sites and severity of pain (p<0.001). CONCLUSIONS: There was a significant association between WoLES and both total pain sites and severity of pain, even after adjusting for potential confounding factors.